MEMBERDAYAKAN KEPRIBADIAN PESERTA DIDIK MELALUI PENDEKATAN QUANTUM LEARNING - Afiful Hair (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2020)
In addition to the knowledge society and learning society, the 21st century is often referred to as the mega era of competition. Therefore, a measure of the success and existence of someone is determined by the ability to compete and the quality they have. Humans have tremendous abilities, both physically, intellectually, and mentally spiritually. If this potential is successfully developed proportionally through a good educational process, it will give birth to perfect humans, humans who excel in the "horizontal and vertical" arena of nature. This paper offers a theory of quantum learning as an alternative approach to the development of a child's personality as a whole. According to the theory developed by Bobby DePorter, education is a life-long project and aims to develop aspects of students' personalities that include intellectual, physical, and emotional. Learning will get optimal results, if done cheerfully and with high self-confidence. Thus increasing motivation and self esteem is an important element to consider in a healthy and happy learning process.